Effect of community based intervention on childhood pneumonia and its risk factors in slums of Dibrugarh, Assam - Nirmolia, Nabanita; Mahanta, Tulika Goswami; Roy, Sailen (Indian Journal of Community Health, 2024)
Background: Pneumonia, one leading cause of mortality in children. Preventing pneumonia related deaths is an urgent priority to meet sustainable development goals. Settings and Design: Community based cross sectional study in two registered slums Chandmarighat and Graham bazar in Dibrugarh, Assam. Methods and Material: 2 out of 10 registered slums were chosen and a baseline cross sectional study was done to list out the risk factors. Based on the risk factors, community based intervention was done by capacity building of frontline workers and monitoring and suportive supervision in one while only monitoring was done in non intervention slum. Taking 95% confidence interval for two tail distribution, the sample size in each of the slums was 300. Statistical analysis: done by using SPSS 20, rates, ratios, proportions, univariate and multivariate analysis. Results: Prevalence of pneumonia was significantly low (9.33% vs 16.33%) in intervention and non-intervention area (p<0.001). Univariate analysis reported that initiation of complementary feeding before 6 months and indoor air pollution were associated with pneumonia in intervened area(p<0.001). Multivariate analysis was done and type of family, complementary feeding before 6 months and indoor air pollution were associated with pneumonia in intervened area. Conclusions: Community based interventions targeting the established risk factors found effective in reducing the childhood pneumonia.